2023
DOI: 10.3390/biomass3030019
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Feasibility of Cloud-Point Extraction for Bioactive Compound Recovery from Food Byproducts: A Review

Theodoros Chatzimitakos,
Vassilis Athanasiadis,
Martha Mantiniotou
et al.

Abstract: In recent years, the production of food biomass waste has been increasing rapidly. This necessitates urgent measures to be taken so as to utilize them. Since most food biomass waste contains useful bioactive substances, cloud-point extraction (CPE) has emerged as a promising solution to valorize waste. CPE is an extraction method employed for the extraction and preconcentration of various chemical compounds, including polyphenols and flavonoids. As with any other extraction procedure, CPE isolates the target c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…It is also important to discuss the feasibility of extraction methods in addition to knowing that the added value of bioactive compounds is high. , The current study showed that the ultrasound-assisted approach resulted in a bioactive component with higher bioactivity. The equipment cost of the UAE method is lower compared to suggested novel methods in the literature, and it also uses less energy during short-term extraction.…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to discuss the feasibility of extraction methods in addition to knowing that the added value of bioactive compounds is high. , The current study showed that the ultrasound-assisted approach resulted in a bioactive component with higher bioactivity. The equipment cost of the UAE method is lower compared to suggested novel methods in the literature, and it also uses less energy during short-term extraction.…”
Section: Resultsmentioning
confidence: 99%
“…The number of surfactant molecules within a micelle is defined as the degree of aggregation. The micelle number can be affected by several factors, such as surfactant type and structure, the properties of the electrolyte, the concentration, the solvent nature, temperature, and the pH level of the solution [ 11 ].…”
Section: Experimental Protocol Of Cpementioning
confidence: 99%
“…Surfactants are chemical substances that can reduce the surface or interfacial tension between two liquids, liquids and gases, or liquids and solids. Bearing a hydrophilic part and a hydrophobic part, surfactants can adsorb onto interfaces and lower the tension of the interfaces [ 11 ]. This improves the interfacial properties of the material and makes it suitable for use in cleaning, surface functionalization, foaming, and emulsification processes [ 25 ].…”
Section: Influencing Parametersmentioning
confidence: 99%
See 2 more Smart Citations